Emotional and Physical Child Abuse in The Context of Natural Disasters: A Focus on Haiti. (December 2019) - Subedi, Sony; Bartels, Susan; Davison, Colleen
ABSTRACT: Objective: To investigate the social and living conditions of households in Haiti before and after the 2010 earthquake and to determine the prevalence of emotional and physical abuse of children aged 2 to 14 in households after the earthquake. Methods: Nationally representative samples of Haitian households from the 2005/2006 and 2012 phases of the Demographic and Health Surveys were used. Descriptive data were summarized with frequencies and measures of central tendency. Chi-squared and independent t tests were used to compare pre-earthquake and post-earthquake data. Basic mapping was used to explore patterns of child abuse in relation to proximity to the epicenter. Results: Comparison of pre-earthquake and post-earthquake data showed noteworthy improvements in the education attainment of the household head and possession of mobile phones after the earthquake. The prevalence of emotional, physical, and severe physical abuse in 2012 was estimated to be 78.5%, 77.0%, and 15.4%, respectively. Mapping revealed no conclusive patterns between the proximity of each region to the epicenter and the prevalence of the different forms of abuse. However, the prevalence of severe physical abuse was notably higher in settlement camps (25.0%) than it was in Haiti overall (15.4%). Conclusions: The high prevalence of child abuse in Haiti highlights an urgent need for interventions aimed at reducing occurrences of household child abuse.